MODELING OF COVID-19 TOPICS ON PUBLIC HEALTH MESSAGE COMMUNICATION PATTERNS ON RADAR BANYUMAS SOCIAL MEDIA - Gita Anggria Resticka; Erwita Nurdiyanto; Gigih Ariastuti Purwandari (Universitas Sebelas Maret, 2023)
The global outbreak of Covid-19 has emerged as one of the most devastating and challenging threats to all peoples of the world. The purpose of this study is to identify the theme and topic of Covid-19 on the pattern of public health message communication on social media Radar Banyumas. The spread of Covid-19 disease was found to correlate with social media activity as a tool to promote Covid-19 News. Topic modeling revealed from time to time in the Radar Banyumas mass media can help understand the impact of the outbreak on the emotions, beliefs, and thoughts of the affected communities. This can open up great opportunities for proper education and dissemination of information on public health recommendations. This study shows that data from Banyumas Radar mass media is useful for infodemiology studies. This topic modeling consistently categorizes public health messages, risk factors, pandemic situations, the impact of Covid-19, measures to slow the spread of Covid-19, preventive measures, health authorities and government policies, negative psychological reactions, social stigma related to Covid-19, Covid-19 cases, Covid-19 in Banyumas, and Covid-19 cases in Indonesia.